Edge effects in grazed and ungrazed Western Australian wheatbelt remnants in relation to ecosystem reconstruction - Majer, Jonathan; Scougall, A.; Hobbs, R. (1993)
This chapter outlines the results of a study of the soil, plants and ant fauna at the edges of fenced and non-fenced remnants of jam (Acacia acuminata)-York gum (Eucalyptus Ioxophleba) woodland in the Kellerberrin district of Western Australia. Specifically, it asks the question "Does farm livestock have a detrimental effect on the abiotic and biotic environment of remnants of native vegetation which are not fenced?" The findings indicate that, for the majority of the habitat variables measured, major differences exist between fenced and nonfenced remnants of vegetation. In comparison to the fenced remnant, the non-fenced remnant had less liner, increased numbers of dead trees, moister, denser soils and elevated levels of soil nutrients. In addition, non-fenced remnants were characterized by reduced tree and shrub abundance, species richness, height and cover, as well as having a greater proportion of non-native herbs. Furthermore, the aggressive, dominant ant functional group (Iridomynnex spp,) formed a greater component of the ant community at non-fenced remnants, whereas the generalized myrmicines were more prevalent at fenced remnants. The main difference between the fenced and non-fenced remnants is that farm livestock can penetrate the non-fenced remnants, livestock are therefore considered to be the principal cause in the decline in environmental quantity of non-fenced remnants.